Plant Elite Squad: First Defense Line and Resistance Genes - Identification, Diversity and Functional Roles. - Wanderley-Nogueira, Ana Carolina; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plants exhibit sensitive mechanisms to respond to environmental stresses, presenting some specific and non-specific reactions when attacked by pathogens, including organisms from different classes and complexity, as viroids, viruses, bacteria, fungi and nematodes. A crucial step to define the fate of the plant facing an invading pathogen is the activation of a compatible Resistance (R) gene, the focus of the present review. Different aspects regarding R-genes and their products are discussed, including pathogen recognition mechanisms, signaling and effects on induced and constitutive defense processes, splicing and post transcriptional mechanisms involved. There are still countless challenges to the complete understanding of the mechanisms involving R-genes in plants, in particular those related to the interactions with other genes of the pathogen and of the host itself, their regulation, acting mechanisms at transcriptional and post-transcriptional levels, as well as the influence of other types of stress over their regulation. A magnification of knowledge is expected when considering the novel information from the omics and systems biology.